2019
DOI: 10.3390/ijms20082042
|View full text |Cite
|
Sign up to set email alerts
|

Role of Metabolic Reprogramming in Epithelial–Mesenchymal Transition (EMT)

Abstract: Activation of epithelial–mesenchymal transition (EMT) is thought to be an essential step for cancer metastasis. Tumor cells undergo EMT in response to a diverse range of extra- and intracellular stimulants. Recently, it was reported that metabolic shifts control EMT progression and induce tumor aggressiveness. In this review, we summarize the involvement of altered glucose, lipid, and amino acid metabolic enzyme expression and the underlying molecular mechanisms in EMT induction in tumor cells. Moreover, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
108
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(114 citation statements)
references
References 166 publications
(174 reference statements)
6
108
0
Order By: Relevance
“…Epithelial‐mesenchymal transition‐dependent tumor invasion and metastasis is accompanied by increased cancer cell stemness and drug resistance . Furthermore, more recent studies report that the EMT is associated with altered metabolism in cancer cells and that EMT‐induced metabolic reprogramming in favor of glycolytic phenotypes promotes tumor aggressiveness . We previously showed that hypoxia and undernutrition increase ANGPTL2 expression in tumor cells and thereby enhance tumor cell metastatic capacity .…”
Section: Discussionsupporting
confidence: 66%
“…Epithelial‐mesenchymal transition‐dependent tumor invasion and metastasis is accompanied by increased cancer cell stemness and drug resistance . Furthermore, more recent studies report that the EMT is associated with altered metabolism in cancer cells and that EMT‐induced metabolic reprogramming in favor of glycolytic phenotypes promotes tumor aggressiveness . We previously showed that hypoxia and undernutrition increase ANGPTL2 expression in tumor cells and thereby enhance tumor cell metastatic capacity .…”
Section: Discussionsupporting
confidence: 66%
“…Epithelial mesenchymal transition (EMT) confers metastatic properties to cancer cells by increasing mobility, invasion, and metastasis (54)(55). Interestingly, SNAI1, the transcription factor that represses Ecadherin expression (the marker of EMT induction), also enhances gene expression patterns that promote glucose uptake and glycolysis (56).…”
Section: Discussionmentioning
confidence: 99%
“…The plasticity of glucose metabolism is important in EMT (34). The genes and biochemical mechanisms impact glucose metabolism during EMT of cancer cells.…”
Section: Glucose Metabolism and Emtmentioning
confidence: 99%
“…HIF1α, Myc and FOXM1 regulate both metabolism and EMT (37). LKB1 / AMPK (Liver kinase B1/AMP-activated protein kinase) downregulates SNAIL and ZEB1and inhibits the invasion and migration of tumor cells, by regulating FOXO3, TGFβ, NF-κB, AKT, and mTOR signaling pathways (34).…”
Section: Glucose Metabolism and Emtmentioning
confidence: 99%
See 1 more Smart Citation